The Impact of Using Snowball Throwing Technique in Improving Students’ Reading Comprehension - Linda Muslita; Sofyan A. Gani (Universitas Syiah Kuala, 2022)
The reason for conducting this research has to do with students’ problem in comprehending English text at second grade SMP Negeri 1 Panga, where many students still faced difficulties in comprehending reading text. This research aims to find out whether the application of Snowball Throwing Technique can improve students’ reading comprehension in terms of identifying main idea, detailed information, and vocabulary. The method used in this study was quantitative research (experimental study) with one group pretest and posttest design. The sample of this research was class VII-1, which consist of 20 students. The researchers used descriptive text as an instrument in collecting the data. In analyzing the data, the researchers used statistical formula. The calculation result showed that the mean score of students’ pretest was 53.67 and the mean score of posttest was 74.67. The hypothesis testing by using a t-test indicates that the obtained t-score was higher than the t-table (91991729), so, the difference is statistically significant, suggesting that the alternative hypothesis (Ha) was accepted, and null hypothesis (Ho) was rejected. Thus, it can be said that the application of Snowball Throwing Technique improved students’ reading comprehension skill. Based on the conclusion above, it is suggested that Snowball Throwing can be used as an alternative technique in teaching reading comprehension.